Pengaruh Pendekatan Kontesktual Bermedia (Powerpoint) dan Sikap Ilmiah Terhadap Hasil Belajar Biologi Peserta Didik SMAN 13 Kabupaten Tebo - Heru Setiadi Putra; Asrial Asrial; Bambang Hariyadi (Edu-Sains: Jurnal Pendidikan Matematika dan Ilmu Pengetahuan Alam, 2014)
The problems encountered in learning biology in SMAN 13 Tebo is the low result in learning biology, and the class average (57 and 58) of minimal completeness (KKM). The causes include the lesson still done traditionally, the class still focus on the teacher as main source of knowledge. Objective of this study to determine the influence of the biology of learning outcomes: the student taught by using media (powerpoint) contextual and those taught by using traditional approach, student of high scientific attitude and low scientific attitude, and presence or absence of interactions between media (powerpoint) contextual approach and scientific attitude toward the biology learning result. This research is an experiment research with factorial design 2x2. Methods research design used in this study is a quasi experimental pratest and postest. The data are analyzed using two way ANOVA. Results of this research indicate that there is a influence in learning result between student taught by using media (powerpoint) contextual and those taught by using traditional approach, there is no influence in learning result between student of high scientific attitude and low scientific attitude, and there is no interaction between media (powerpoint) contextual approach and scientific attitude toward the biology learning result.